KEPASTIAN HUKUM DAN AKIBAT HUKUM TERHADAP PEMUTUSAN HUBUNGAN KERJA KARENA PENOLAKAN MUTASI OLEH PEKERJA (STUDI KASUS TERHADAP PUTUSAN MAHKAMAH AGUNG NOMOR 461 K/PDT.SUS-PHI/2017) - Vania Safira Putri; Ahmad Redi (Jurnal Hukum Adigama, 2020)
As living beings, people have to have various needs that shall be fulfilled to sustain their life. Every people shall work to fulfill their necessities of life. People may work by being an entrepreneur or as an employee to work for any employer. Sometimes, the employer gives an order to mutate an employee from a position to another. But often, the mutations gives are not in accordance with the employee’s skills and passions resulting in the mutation refusal from the employee. As a result of the refusal, often the employee is considered not obey a working order given by the employer, the employee is considered not carrying out the work order and may be subject to sanctions, including Termination of Employment. The result of the study reveals that there is legal uncertainty in the regulation with regard to whether or not a refusal of mutation by an employee shall be used as a valid reason to terminate the employee. Furthermore, it can result in a contradiction between one court decision and another.